Improved degradation of petroleum hydrocarbons by co-culture of fungi and biosurfactant-producing bacteria. (March 2022) - Atakpa, Edidiong Okokon; Zhou, Hanghai; Jiang, Lijia; Ma, Yinghui; Liang, Yanpeng; Li, Yanhong; Zhang, Dongdong; Zhang, Chunfang
Abstract: Microbial remediation has proven to be an effective technique for the cleanup of crude-oil contaminated sites. However, limited information exists on the dynamics involved in defined co-cultures of biosurfactant-producing bacteria and fungi in bioremediation processes. In this study, a fungal strain ( Scedosporium sp. ZYY) capable of degrading petroleum hydrocarbons was isolated and co-cultured with biosurfactant-producing bacteria ( Acinetobacter sp. Y2) to investigate their combined effect on crude-oil degradation. Results showed that the surface tension of the co-culture decreased from 63.12 to 47.58 mN m −1, indicating the secretion of biosurfactants in the culture. Meanwhile, the degradation rate of total petroleum hydrocarbon increased from 23.36% to 58.61% at the end of the 7-d incubation period. In addition, gas chromatography – mass spectrometry analysis showed a significant ( P  < 0.05) degradation from 3789.27 mg/L to 940.33 mg/L for n -alkanes and 1667.33 μg/L to 661.5 μg/L for polycyclic aromatic hydrocarbons. Moreover, RT-qPCR results revealed the high expression of alkB and CYP52 genes by Acinetobacter sp. Y2 and Scedosporium sp. ZYY respectively in the co-culture, which corelated positively ( P  < 0.01) with n -alkane removal. Finally, microbial growth assay which corresponded with Fluorescein diacetate hydrolysis activity, highlighted the synergistic behavior of both strains in tackling the crude oil. Findings in this study suggest that the combination of fungal strain and biosurfactant-producing bacteria effectively enhances the degradation of petroleum hydrocarbons, which could shed new light on the improvement of bioremediation strategies. Graphical abstract: Image 1 Highlights: An effective strategy was proposed for the treatment of petroleum pollutants. 80% medium n -alkanes (C11–C20) were effectively removed in the co-culture. The co-culture induced high expression of some degradative genes and key enzymes. Abundance of genes positively co-related with n -alkanes degradation. Fungi eventually impeded the growth of bacteria.